Early rehabilitation of bilateral cleft lip and palate patients using an orthopaedic appliance and gingivo-periosteoplasty: pilot study - Cerón-Zapata, Ana María; López-Palacio, Ana María; Cano-Acosta, Alonso Enrique; Toro-Herrera, Sergio Alejandro; Ramírez, Elizabeth (Revista Facultad de Odontología Universidad de Antioquia, 2009)
Introduction: premaxilla repositioning in cases of bilateral cleft lip and palate (BCLP) by means of intraoral devices has been a controversial aspect in its treatment. This study presents a therapeutic proposal for early intraoral dynamic orthopedics for out community. The objective was to evaluate the results obtained by using a mucosa bony supported intra oral device along with gingiva-periostioplasty surgery as part of the initial lip closure in cases of complete BCLP. Methodology: 4 babies with complete BCLP, 20 weeks old were evaluated, 3 boys and 1 girl. Every patient received an intra oral mucosa bony supported device. After the orthopedic result, a primary rhino cheiloplasty and a gingival periostioplasty were performed. Models of the upper arch were compared before and after the orthopedic treatment with digital measurements that were then subjected to descriptive statistical analysis; bone formation was evaluated by means of computerized tomography 6 months after the gingival periostioplasty. Results: every patient achieved retraction of the maxilla and a satisfactorily alveolar alignment. There was bone formation in 3 of the 6 sites in which the gingival-periosteoplasty was performed. Conclusions: pre-surgical orthopedic treatment with an intraoral-appliance can successfully improve mal-alignment of the pre-maxilla in patients with bilateral cleft lip and palate, and allows bone formation when it is followed by gingival-periosteoplasty. This protocol represents a practical option for treatment in cases with protrusion of the pre-maxilla in our community.